2018
DOI: 10.1002/cpe.4895
|View full text |Cite
|
Sign up to set email alerts
|

Marine bathymetry processing through GPGPU virtualization in high performance cloud computing

Abstract: Fast technology development has influenced the widespread use of low-power devices in different scientific, environmental, and everyday life areas, giving birth to the Internet of Things.In this paper, we focus on the context of marine studies, addressing the problem of marine bathymetry data processing and analysis via pervasive and Internet-connected sensors and low-power distributed devices. Pervasive and Internet-connected low-power devices (as the components involved in the sensing and processing actions)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Further improvements of the system will be represented by the enhancement of the model chain resolution thanks to the progress in cloud computing (Montella et al, 2015) as well as to the approach based on GPGPU (general-purpose computing on graphics processing units) (Di Lauro et al, 2012;Montella et al, 2018;Marcellino et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further improvements of the system will be represented by the enhancement of the model chain resolution thanks to the progress in cloud computing (Montella et al, 2015) as well as to the approach based on GPGPU (general-purpose computing on graphics processing units) (Di Lauro et al, 2012;Montella et al, 2018;Marcellino et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This methodology, giving rise to the signal reported in Fig. 6e, is described in the extensive literature on coastal video monitoring (Takewaka and Nakamura, 2001;Ojeda et al, 2008;Zhang and Zhang, 2008). According to Vousdoukas et al (2012b), the run-up excursion was identified by using the threshold method supplied by Otsu (1975), which is able to identify the wet-dry boundary by pixel colour.…”
Section: Altimeter and Video Monitoringmentioning
confidence: 99%
“…Further improvements of the system will be represented by the enhancement of the model chain resolution thanks to the progress in cloud computing (Montella et al, 2015) as well as to the approach based on GPGPU (general-purpose computing on graphics processing units) (Di Montella et al, 2018;Marcellino et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In “Marine Bathymetry Processing Through GPGPU Virtualization in High Performance Cloud Computing” by Montella et al, the authors address the problem of marine bathymetry data processing and analysis via pervasive and internet‐connected sensors and low‐power distributed devices, by implementing a GP‐GPU virtualization service, for achieving high performance geographical data interpolation in a cloud computing scenario.…”
Section: Themes Of the Special Issuementioning
confidence: 99%